Analisis Hukum Islam Terhadap “Perkawinan Asakan” di Kecamatan Pameungpeuk Kabupaten Bandung - Muhamad Fahmi Rizaldi; Encep Abdul Rojak; Fahmi Fatwa Rosadi Satria Hamdani (Bandung Conference Series: Islamic Family Law, 2024)
Abstract. Business The legal issues studied regarding promiscuous marriages at the Religious Affairs Office, Pameungpeuk District, Bandung Regency. This research has three problems which include asakan marriage, registration, and lebe, where these three problems are interrelated. This is the background for conducting this research in depthThe purpose of this research is to find out what a forced marriage is and review it from the perspective of munakahat jurisprudence and according to the Marriage LawThe method used by the author is juridical-empirical. The type of research data is qualitative data and research data collection techniques are carried out by means of interviews, observations and literature studiesAsakan marriage is the term for a private marriage or a religious marriage accompanied by a lebe. If you look at it from the jurisprudence of law, this marriage is valid because all the legal pillars of marriage are fulfilled, but there is fraud or circumventing the registration procedure which should be done in the religious court. Abstrak. Masalah hukum yang diteliti mengenai perkwinan asakan di Kantor Urusan Agama Kec Pameungpeuk Kab Bandung. Penelitian tersebut memiliki tiga masalah yang mencangkup perkawinan asakan, pencatatan, dan lebe yang dimana ketiga masalah tersebut saling berkaitan. Hal tersebut yang menjadi latar belakang dilakukannya penelitian ini secara mendalam.Tujuan penelitian ini adalah untuk mengetahui apa itu perkawinan asakan serta tinjauan menurut perspektif fikih munakahat dan menurut UU Perkawinan, Metode yang digunakan oleh penulis adalah yuridis-empiris.Jenis data penelitiannya adalah data kualitatif dan teknik pengumpulan data penelitian dilakukan dengan cara wawancara, obserpasi dan studi kepustakaan.Perkawinan asakan merupakan istilah dari perkawinan di bawah tangan atau pernikahan agama yang di dampingi oleh lebe, jika di tinjau dari fikih munkahat perkawinan ini sah karena sarat sah rukun nikah nya terpenuhi namun terjadi pengakalan atau mengsiasati prosedur pencatatan yang seharus nya di isbat nikahkan di pengadilan agama.